A Patient with Giant Rippled-Pattern Sebaceoma in the Occipital Region - Masayuki Takahashi; Masaru Arima; Yohei Iwata; Kayoko Suzuki; Yoshikazu Mizoguchi; Makoto Kuroda; Kayoko Matsunaga (Karger Publishers, 2016)
A 72-year-old male visited a nearby hospital with a large tumor in his occipital region, which had existed since 20 years. Since malignant tumor was suspected, he was referred to our department. At the initial consultation, an elastic-hard, yellow-brown, sessile tumor, measuring 8 × 7 × 5 cm and with a flat surface, was observed in the occipital region. The tumor was resected and covered with artificial dermis. Histopathologically, the lesion was composed of basal-cell-like cells with nest formation in the dermis. A rippled pattern, or the single-line arrangement of tumor cells involving the stroma, was present. In addition, some tumor clusters revealed the differentiation to sebaceous glands, and these cells were positive for cytokeratin (AE1/AE3) and epithelial membrane antigen, which is consistent with the staining of sebaceous glands. On the contrary, tumor cells were negative for epithelial antigen (Ber-EP4), and Ki67 (MIB1) index was 5% or lower. Therefore, we diagnosed the tumor as rippled-pattern sebaceoma and not as basal cell carcinoma. Although this case was quite unique in its large size, immunostaining was useful for the definite diagnosis.